Music Theory: Speculation, Reasoning, Experience. A Perspective from Systematic Musicology - Albrecht Schneider (Zeitschrift der Gesellschaft für Musiktheorie)
Music theory at present comprises a broad range of concepts and approaches. Besides historical research devoted to the reconstruction and interpretation of source material relevant to (‘western’) music theory, one finds studies with a focus on the description of individual works or on the ‘poetics’ of certain composers. In this respect, music theory is closely connected to music analysis and aesthetics. In the past decades, perceptual and cognitive issues have been included more often also in studies in music theory and analysis. Further, music theory is regarded to make up an ‘applied’ discipline whose goal is to teach basic musical skills, and thus to serve a ‘practical’ purpose, in the first place. Though these orientations all seem legitimate and of relevance to music theory, one should neither neglect the philosophical and scientific background of the discipline nor the need to carry out empirical and experimental investigations that have been part of music theory since antiquity. In the present article a perspective mainly chosen from the history of ideas is combined with some empirical data and demonstrations in order to elucidate a concept of music theory that continues traditions of fundamental music research.